EVALUASI DAMPAK PELAKSANAAN PERATURAN DAERAH NOMOR 1 TAHUN 2012 TERHADAP PEMUNGUTAN PAJAK HIBURAN DI DINAS PENDAPATAN DAERAH KOTA JAYAPURA - Aryastuti, Nia; Noak, Piers Andreas; Supriliyani, Ni Wayan (CITIZEN CHARTER, 2015)
ABSTRACT Dispenda is one of the agencies that has general function as administrative and public service provider related to taxes and retributions, one of managed taxes is entertainment tax. Contributions of entertainment tax managed by the local revenue office for the last three years are relatively increasing and always reaching the target. However, these contributions are not accompanied by taxpayers compliance to fullfil their tax obligations. This study will discuss the mechanism and obstacles of entertainment tax collection in the local revenue office. This study was using qualitative descriptive design. The results from this study show that implementation of entertainment tax collection has been good enough, based on public service quality indicators and tax collection policy concepts that have been used majorly. Keywords: Dispenda, Taxpayer, Public Service Quality, Entertainment Tax Collection.